Hypofractionated Radiotherapy for Anaplastic Thyroid Carcinoma: 15 Years of Experience in a Single Institution. Issue 1 (4th January 2019) - Takahashi, Noriyoshi; Matsushita, Haruo; Umezawa, Rei; Yamamoto, Takaya; Ishikawa, Yojiro; Katagiri, Yu; Tasaka, Shun; Takeda, Kazuya; Fukui, Katsuya; Kadoya, Noriyuki; Ito, Kengo; Jingu, Keiichi
Abstract : Background: Anaplastic thyroid carcinoma (ATC) is a rare cancer and has a poor prognosis. Several radiation protocols have been reported, but the results were not satisfactory. Objective: The aim of this study was to determine the effect of hypofractionated radiotherapy. Methods: Thirty-three patients who received radiotherapy for ATC between January 2000 and December 2014 were retrospectively included. We defined hypofractionated radiotherapy as a single dose ≥5 Gy. Results: Nineteen patients were treated with hypofractionated radiotherapy. Twenty-eight patients died, and 27 of those patients died from ATC. Sixteen patients died from distant metastasis and 6 from local recurrence. In the hypofractionated radiotherapy group, local recurrence occurred in 5 patients and 1 of them died from active bleeding from a local tumor. There was local recurrence in 7 patients who received the other protocol, and 5 of them died from asphyxiation, active bleeding, or uncontrollable growth of a local tumor on the neck. The median overall survival (OS) was 5 months. In multivariate analysis, patients who received an equivalent dose in 2-Gy fractions (EQD2 ) ≥50 Gy had significantly better OS ( p = 0.016). In univariate analysis, patients who received hypofractionated radiotherapy did not have significantly better OS ( p = 0.872) or local control ( p = 0.090). The χ 2 test showed that significantly fewer patients died from local recurrence in the hypofractionated radiotherapy group ( p = 0.025). Conclusions: Multivariate analysis showed that an EQD2 ≥50 Gy resulted in better OS, and hypofractionated radiotherapy decreased the rate of mortality from local recurrence.